Medullary thyroid carcinoma spindle cell variant: a rare case report - Singh, Swati; Singh, Sanjeev Kumar; Maurya, Geeta; Rashmi (International Journal of Research in Medical Sciences, 2023)
Medullary thyroid carcinoma (MTC) accounts for only 4% of thyroid tumors and originates from parafollicular cells secreting calcitonin. However, it accounts for 13% of all thyroid cancer related death. We herein report a case of 50 years male who presented with a right neck swelling measuring 3×2×2 cm for 2 years, which was gradually increasing. Ultrasonography of the neck revealed a hypoechoic nodule in the right lobe of thyroid. There was no relevant family history. Patient was clinically euthyroid. Fine needle aspiration smears showed many dispersed spindle shaped cells and loosely cohesive clusters of cells. Nuclei of these cells are spindle shaped and showing moderate anisokaryosis. Clumps of hyaline material also seen. A provisional diagnosis of MTC spindle cell variant had been made, which was confirmed by histopathology. Early diagnosis of MTC is very important. Because if patient do not have metastatic disease usually cured by total thyroidectomy.